MUNICIPALITIES AND THE MEGA-EVENT - Phillips, Carol (My University, 2012)
Why do municipalities bid for mega-events? Simply bidding for these events, such as the Commonwealth Games, the Olympic Games or a World Expo, can run into the millions of dollars. The cost of hosting such a large-scale international event now runs into the billions of dollars. It would appear to be an economic risk, yet cities, and their respective countries, around the world continue to choose this public policy path. Using urban regime theory, and focusing on the work of Stone, Stoker and Mossberger, this research investigates the actors and their motivations surrounding the Commonwealth Games bids by Melbourne, Australia for 2006, Halifax, Nova Scotia for 2014, and Hamilton, Ontario for 1994, 2010 and 2014. Civic pride, economic development, tourism growth and infrastructure improvements are all motivating factors and a mega-event is seen as a short-cut to achieving these public policy goals. We conclude that strong cooperation between the public and private sectors is necessary, as well as comparable cooperation between the upper levels of government and the host city, for a seriously competitive bid in a Western democracy, and that the weaker the cooperation, the less resolve and likelihood there is to host an expensive event at any cost. This research not only furthers political science knowledge in the sports public policy field, but also confirms the use of urban regime theory as a useful framework in comparative urban analysis as it allows us to categorize actors and motivations as we compare across municipalities.
Keywords: mega-event; Commonwealth Games; urban regime theory; Melbourne; Halifax; Hamilton; Public Policy; Public Policy